In‐vivo occlusal caries prevention by pulsed CO2‐laser and fluoride varnish treatment—A clinical pilot study. Issue 5 (4th June 2013) - Rechmann, Peter; Charland, Daniel A.; Rechmann, Beate M.T.; Le, Charles Q.; Featherstone, John D.B.
Abstract Background and Objectives High caries prevalence in occlusal pits and fissures warrants novel prevention methods. An 86% reduction in dental enamel smooth surface demineralization in‐vivo following short‐pulsed 9.6 µm‐CO2‐laser irradiation was recently reported. The objective of this study was to conduct a blinded 12‐month‐pilot clinical trial of occlusal pit and fissure caries inhibition using the same CO2‐laser irradiation conditions. Study Design/Materials and Methods Twenty subjects, average age 14 years, were recruited. At baseline, second molars were randomized into test and control groups, assessed by International Caries Detection & Assessment System (ICDAS‐II), SOPROLIFE light‐induced fluorescence evaluator in daylight and blue‐fluorescence mode and DIAGNOdent. An independent investigator irradiated test molars with a CO2‐laser, wavelength 9.6 µm, pulse‐duration 20 µs, pulse‐repetition‐rate 20 Hz, beam diameter 800 µm, average fluence 4.5 ± 0.5 J/cm2, 20 laser pulses per spot. At 3‐, 6‐ and 12‐month recall teeth were assessed by ICDAS, SOPROLIFE and DIAGNOdent. All subjects received fluoride varnish applications at baseline and 6‐month recall. Results All subjects completed the 3‐month, 19 the 6‐month and 16 the 12‐month recall. At all recalls average ICDAS scores had decreased for the test and increased for the control fissures (laser vs. control, 3‐month: −0.10 ± 0.14, 0.30 ± 0.18, P > 0.05; 6‐month: −0.26 ± 0.13, 0.47 ± 0.16, P = 0.001; 12‐month: −0.31 ± 0.15, 0.75 ± 0.17, P < 0.0001; mean ± SE, unpaired t‐test) being statistically significantly different at 6‐ and 12‐month recalls. SOPROLIFE daylight evaluation revealed at 6‐ and 12‐months statistically significant differences in changes between baseline and recall for test and control molars, respectively (laser vs. control, 6‐month: 0.22 ± 0.13, 0.17 ± 0.09, P = 0.02; 12‐month: 0.28 ± 0.19, 0.25 ± 0.17, P = 0.03). For SOPROLIFE blue‐fluorescence evaluation mean changes in comparison to baseline for the control and the laser treated teeth were also statistically significant for the 6‐ and 12‐month recall. Conclusion Specific microsecond short‐pulsed 9.6 µm CO2‐laser irradiation markedly inhibits caries progression in pits and fissures in comparison to fluoride varnish alone over 12 months. Lasers Surg. Med. 45:302–310, 2013. © 2013 Wiley Periodicals, Inc.